Integrating Digital Payment and Monitoring Systems in On-Street Parking Services: A Cyber-Physical System Approach - Nursuwars, Firmansyah Maulana Sugiartana; Andang, Asep; Shofa, Rahmi Nur; Sambas, Aceng (IAICO, 2025)
On-street parking is a critical component of urban mobility but often encounters challenges in terms of payment efficiency, transparency, and system supervision. This study aims to develop an on-street parking service system based on a Cyber-Physical System (CPS) that integrates digital payments via QRIS and Android Point of Sale (POS) devices. The proposed system is designed to streamline transaction processes, enhance accountability of parking attendants, and provide real-time monitoring data accessible to system administrators. The research methodology combines the Software Development Life Cycle (SDLC) and Hardware Development Lifecycle, with a modular system architecture and comprehensive functional testing. The results show that the system can process transactions in an average of 23 seconds, supports automated digital records, and improves user satisfaction with parking services. The implications of this development extend beyond digital transformation in the transportation sector, offering a foundation for data-driven and adaptive smart parking management. This study contributes to the advancement of efficient, transparent, and user-centered public service systems through integrated technological solutions.